2016
DOI: 10.1210/jc.2015-3089
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Plasma DHA Levels Increase Prior to 29 Days Post-LH Surge in Women Undergoing Frozen Embryo Transfer: A Prospective, Observational Study of Human Pregnancy

Abstract: An increase in maternal plasma DHA concentration is initiated in human pregnancy prior to neural tube closure which occurs at 28 d gestation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…Previous data has shown the importance of DHA during the latter stages of pregnancy when the brain accrues its tissue mass [ 29 ]. More recently, however, it has been shown that DHA is also vital at the stage of when the neural tube closes at day 28 of gestation [ 30 ]. Due to its importance, there are specific recommendations for DHA intake for pregnant and lactating women.…”
Section: Discussionmentioning
confidence: 99%
“…Previous data has shown the importance of DHA during the latter stages of pregnancy when the brain accrues its tissue mass [ 29 ]. More recently, however, it has been shown that DHA is also vital at the stage of when the neural tube closes at day 28 of gestation [ 30 ]. Due to its importance, there are specific recommendations for DHA intake for pregnant and lactating women.…”
Section: Discussionmentioning
confidence: 99%
“…The omega-3 long chain polyunsaturated fatty acids (n-3 LCPUFA) are comprised of eicosapentaenoic acid (EPA), docosapentaenoic acid (DPA) and docosahexaenoic acid (DHA). DHA and arachidonic acid are important fatty acids for neurological development [1,2]. DHA is the most abundant n-3 LCPUFA in the brain and its role in the brain has been described in a recent review [3].…”
Section: Introductionmentioning
confidence: 99%
“…The health benefits of omega-3 long-chain polyunsaturated fatty acids ( n -3 LCPUFAs) are numerous and include neurological development [ 1 , 2 , 3 ], improved cognition [ 4 , 5 , 6 ], and reduced cognitive decline [ 7 ] as well as cardiovascular disease (CVD) benefits [ 8 ].…”
Section: Introductionmentioning
confidence: 99%